Ischemic stroke associated with adenomyosis-related abnormal uterine bleeding: a systematic review of management and outcomes - Zheng, Limei; Zhang, Hong; Fang, Wei; Yang, Jianhua (Frontiers in Neurology, 2025)
BackgroundAdenomyosis is frequently associated with abnormal uterine bleeding (AUB) and anemia. In the setting of arterial stenosis or hypercoagulability, AUB may precipitate ischemic stroke. However, the optimal management strategy remains unclear.MethodsIn accordance with PRISMA 2020, we systematically searched PubMed, Web of Science, CNKI, and Wanfang from inception to November 20, 2024, without language restrictions. Eligible studies were human case reports or case series that described adenomyosis-associated ischemic stroke with extractable data on management and outcomes. Data extraction was performed independently by two reviewers, and risk of bias was assessed using the JBI tool. A descriptive synthesis was conducted, and Fisher’s exact tests were applied where appropriate.ResultsEighteen studies involving 24 patients fulfilled the inclusion criteria. Among these patients, 66.7% experienced stroke onset during menstruation, 85.7% presented with anemia, and more than 95% showed elevated CA125 and D-dimer levels. Stroke recurrence occurred in 55.6% of patients who received conservative management, compared with 0% of those who underwent hysterectomy (Fisher’s exact p ≈ 0.005). In menstruation-related cases managed conservatively, the recurrence rate reached 83.3%.ConclusionCurrent evidence indicates that rapid uterine hemostasis may facilitate timely initiation of antithrombotic therapy and thereby reduce recurrence risk in adenomyosis-associated stroke. Surgical management, particularly hysterectomy, appears more effective than conservative therapy in carefully selected high-risk patients. Larger prospective studies are needed to confirm these findings and to refine management strategies.